Contract work at older ages. (7th July 2021) - Abraham, Katharine G.; Hershbein, Brad; Houseman, Susan N.
Abstract: The share of workers who are self-employed rises markedly with age. Given policy concerns about inadequate retirement savings, especially among those with lower education, and the resulting interest in encouraging employment at older ages, it is important to understand the role that self-employment arrangements play in facilitating work among seniors. New data from a survey module fielded on a Gallup telephone survey distinguish independent contractor work from other self-employment and provide information on informal and online platform work. The Gallup data show that, especially after accounting for individuals who are miscoded as employees, self-employment is even more prevalent at older ages than suggested by existing data. Work as an independent contractor is the most common type of self-employment. Roughly one-quarter of independent contractors aged 50 and older work for a former employer. At older ages, self-employment generally – and work as an independent contractor specifically – is more common among the highly educated, accounting for much of the difference in employment rates across education groups. We provide suggestive evidence that differences in opportunities for independent contractor work play an important role in the lower employment rates of less-educated older adults.